Recent progress on the corrosion characterization of magnesium (Mg) prepared by powder metallurgy technique - M. A. F., Romzi; Juliawati, Alias; M. I. M., Ramli (IOP Publishing, 2021)
This paper reviews the progress on the corrosion characterization of magnesium (Mg)based material prepared by the powder metallurgy (PM) technique. In recent years, Mg alloys and composites produced by the powder metallurgy technique have been gaining interest in many industries especially in biomedical applications. Mg is also being used to improve battery electrodes and be considered for next-generation secondary batteries with remarkable energy and capacity density. Nevertheless, bare Mg is known to have poor corrosion resistance in most environments with occurrences such as non-uniform corrosion attack, high and fast reaction, microgalvanic corrosion of Mg-matrix and intermetallic particle and formation of non-protective hydroxide film after longer exposure in corrosive environment. New fabrication methods of Mg, such as the PM method are likely to benefit future Mg's mechanical and corrosion properties. Utilizing the latest corrosion characterization method is needed to ensure accurate and precise methods for investigating corrosion behaviour. The recent approach and progress in characterizing Mg's corrosion behaviour, specifically that have been prepared by the PM technique is considered in this paper.